Детективний і шпигунський роман: «клітинна» модель жанроутворення - Норец, М.В. (Культура народов Причерноморья, 2014)
«Клітинна» модель жанроутворювання, запропонована автором, представляє собою
динамічні відносини між жанровою матрицею та жанровою домінантою, результатом яких є
формування нового жанру. Зміни у жанровій матриці зумовлені впливом багатьох зовнішніх факторів.
Акумулювання динамічних ознак у жанровій домінанті дає можливість формуванню нового жанру.
Детективний роман є материнською матрицею для формування жанру шпигунського роману. Клеточная модель жанроформирования, предложенная автором, представляет собой
динамические отношения между жанровой матрицей и жанровой доминантой, результатом которых
выступает формирование нового жанра. Изменения в жанровой матрице обусловлены влиянием многих
внешних факторов. Аккумуляция динамических признаков жанровой доминанты даёт возможность
формирование нового жанра. Детективный роман выступает материнской матрицей для образования
жанра шпионского романа. “Cellar” model of genre forming, offered by the author looks like the dynamic relations between
genre matrix and genre dominant, the results of which is the forming of a new genre. Changes in genre matrix
are influenced by many outer factors. The accumulation of the dynamic features of genre dominant gives the
possibility for forming the new genre. Under the influence of historic, political, social, literary factors the genre matrix of detective novel undergoes some certain processes inside, which give the reason for the changes
dictated by the time, gaining new features in the genre dominant. When the amount of changes in the genre
dominant becomes more than the amount of genre paradigm of the detective genre, the genre dominant of the
detective novel gets separated and becomes a new genre matrix, the matrix of the spy novel. The author of the
article presents the “cellar” model of genre forming where the mechanism of genre transformation is
highlighted. In the article, the scheme of genre matrix and genre dominant as well as the genre matrix of a new
genre are presented.